2022
DOI: 10.1088/1361-648x/ac6a9a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of an FeCrMoCBY metallic glass revealed by high energy x-ray diffraction

Abstract: Amorphous bulk metallic glasses with the composition Fe48Cr15Mo14C15B6Y2 have been of interest due to their special mechanical and electronic properties, including corrosion resistance, high yield-strength, large elasticity, catalytic performance, and soft ferromagnetism. Here, we apply a reverse Monte Carlo technique to unravel the atomic structure of these glasses. The pair-distribution functions for various atomic pairs are computed based on the high-energy x-ray diffraction data we have taken from an amorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The RMC method can provide snapshot views of about 10 4 atoms, which is much larger than the number of atoms conventionally used in first-principles simulations [38,39], although efficient exploitation of high-performance computing resources is continuing to extend the reach of these precise computational methods to increasingly larger molecular and condensed matter systems [40]. If the RMC fit is consistent with all the data available, then the resulting configuration will accurately capture the structural characteristics of the sample being studied.…”
Section: Reverse Monte Carlo Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMC method can provide snapshot views of about 10 4 atoms, which is much larger than the number of atoms conventionally used in first-principles simulations [38,39], although efficient exploitation of high-performance computing resources is continuing to extend the reach of these precise computational methods to increasingly larger molecular and condensed matter systems [40]. If the RMC fit is consistent with all the data available, then the resulting configuration will accurately capture the structural characteristics of the sample being studied.…”
Section: Reverse Monte Carlo Analysis and Resultsmentioning
confidence: 99%
“…If the RMC fit is consistent with all the data available, then the resulting configuration will accurately capture the structural characteristics of the sample being studied. Along these lines, Pussi et al [39] have shown how the atomic structure of the FeCrMoCBY metallic glass can be resolved by combining density functional theory (DFT) calculations with a PDF analysis.…”
Section: Reverse Monte Carlo Analysis and Resultsmentioning
confidence: 99%